Pediatric melioidosis in Sarawak, Malaysia: Epidemiological, clinical and microbiological characteristics - Anand, Mohan; Yuwana, Podin; Tai, Nickson; Chieng, Chae Hee; Vanessa, Rigas; Machunter, Barbara; Mayo, Mark; Wong, Desiree; Chien, Su Lin; Tan, Lee See; Goh, Charles; Bantin, Reginal; et al. (PLOS, 2017)
Background Melioidosis is a serious, and potentially fatal community-acquired infection endemic to northern Australia and Southeast Asia, including Sarawak, Malaysia. The disease, caused by the usually intrinsically aminoglycoside-resistant Burkholderia pseudomallei, most commonly affects adults with predisposing risk factors. There are limited data on pediatric melioidosis in Sarawak.